Effects of whole grain rye, with and without resistant starch type 2 supplementation, on glucose tolerance, gut hormones, inflammation and appetite regulation in an 11–14.5 hour perspective; a randomized controlled study in healthy subjects - Sandberg, Jonna C. (Nutr J, 2017)
BACKGROUND: The prevalence of obesity is increasing worldwide and prevention is needed. Whole grain has shown potential to lower the risk of obesity, cardiovascular disease and type 2 diabetes. One possible mechanism behind the benefits of whole grain is the gut fermentation of dietary fiber (DF), e.g. non-starch polysaccharides and resistant starch (RS), in whole grain. The purpose of the study is to investigate the effect of whole grain rye-based products on glucose- and appetite regulation. METHOD: Twenty-one healthy subjects were provided four rye-based evening test meals in a crossover overnight study design. The test evening meals consisted of either whole grain rye flour bread (RFB) or a 1:1 ratio of whole grain rye flour and rye kernels bread (RFB/RKB), with or without added resistant starch (+RS). White wheat flour bread (WWB) was used as reference evening meal. Blood glucose, insulin, PYY, FFA, IL-6 as well as breath H(2) and subjective rating of appetite were measured the following morning at fasting and repeatedly up to 3.5 h after a standardized breakfast consisting of WWB. Ad libitum energy intake was determined at lunch, 14.5 h after evening test and reference meals, respectively. RESULTS: The evening meal with RFB/RKB + RS decreased postprandial glucose- and insulin responses (iAUC) (P < 0.05) and increased the gut hormone PYY in plasma the following morning 0–120 min after the standardized breakfast, compared to WWB (P = 0.01). Moreover, RFB increased subjective satiety and decreased desire to eat, and both RFB and RFB/RKB decreased feeling of hunger (AUC 0–210 min). All rye-based evening meals decreased or tended to decrease fasting FFA (P < 0.05, RFB/RKB: P = 0.057) and increased breath hydrogen concentration (0–120 min, P < 0.001). No effects were noted on energy intake at lunch or inflammatory marker IL-6 (0 + 180 min) after the rye-based evening meals, compared to WWB. CONCLUSION: Whole grain rye bread has the potential to improve cardiometabolic variables in an 11–14.5 h perspective in healthy humans. The combination RFB/RKB + RS positively affected biomarkers of glucose- and appetite regulation in a semi-acute perspective. Meanwhile, RFB and RFB/RKB improved subjective appetite ratings. The effects probably emanate from gut fermentation events. TRIAL REGISTRATION: The study was registered at: ClinicalTrials.gov, register number NCT02347293 (www.clinicaltrials.gov/ct2/show/NCT02347293). Registered 15 January 2015.